Assessment of the oral health condition of nursing home residents by primary care nurses. (20th February 2014) - Gerritsen, P.F.M.; Schrijvers, A.J.P.; Cune, M.S.; van der Bilt, A.; de Putter, C.
ABSTRACT We interviewed 36 primary care nurses in three Dutch nursing homes regarding the functional oral health and dental treatment needs of 331 care‐dependent residents (average age 77.8 years). The nurses assessed the residents' oral health condition as good (8.3 on a scale of 0 to 10). Edentulous residents wearing dentures were considered to have better functional oral health than dentate residents wearing partial dentures and edentulous residents not wearing dentures. According to the nurses, only 9% of the residents required dental treatment. This finding is in contrast with an intraoral study of the same population, in which dentists determined that 73% of the residents needed dental treatment.